(untitled) (MATEMATIKA, 2011)
Accurate approximations for the Stieltjes integral by the generalized midpoint rule. The generalized midpoint rule is established on the notion of the derivative of function with respect to the strictly increasing function defined in [9]. Keywords: Stieltjes integral; generalired midpoint rule; the derivative of the function with respect to the strictly increasing function; generalized formula of Taylor. 2010 Mathematics Subject Classification 26D15; 26A42.